1997
DOI: 10.1007/s004410050785
|View full text |Cite
|
Sign up to set email alerts
|

Transthyretin distribution in the developing choroid plexus of the South American opossum ( Monodelphis domestica )

Abstract: The distributions of transthyretin and albumin in the choroid plexus during brain development have been compared. The South American opossum was chosen because the young are born around the time of choroid plexus formation. Previous work showed that in the adult opossum, transthyretin is expressed in the choroid plexus cells. However, systematic studies of transthyretin in the choroid plexus during development have not been carried out before. Transthyretin was present in 90-95% of the choroidal cells form bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…These studies, using immunocytochemistry, showed that a number of common plasma proteins (albumin, fetuin, ␣-fetoprotein, transthyretin, and transferrin) are found in epithelial cells of immature choroid plexuses at all three sites at which choroid plexuses are found, IIIrd, IVth, and lateral ventricles. The quantitative studies of Jacobsen et al (1982aJacobsen et al ( ,b, 1983, Knott et al (1997), and Li et al (1997) confirmed the semi-quantitative impression that positive cells are much more frequent in immature choroid plexuses and that staining is absent in choroid plexuses of the more mature brain, with the exception of transthyretin. Transthyretin distribution also differs from other plasma proteins in that it is present in almost all choroid plexus epithelial cells at all ages, whereas other plasma proteins are only present in a small proportion of the cells.…”
Section: Morphological Development Of the Choroid Plexus Light Microsmentioning
confidence: 73%
See 2 more Smart Citations
“…These studies, using immunocytochemistry, showed that a number of common plasma proteins (albumin, fetuin, ␣-fetoprotein, transthyretin, and transferrin) are found in epithelial cells of immature choroid plexuses at all three sites at which choroid plexuses are found, IIIrd, IVth, and lateral ventricles. The quantitative studies of Jacobsen et al (1982aJacobsen et al ( ,b, 1983, Knott et al (1997), and Li et al (1997) confirmed the semi-quantitative impression that positive cells are much more frequent in immature choroid plexuses and that staining is absent in choroid plexuses of the more mature brain, with the exception of transthyretin. Transthyretin distribution also differs from other plasma proteins in that it is present in almost all choroid plexus epithelial cells at all ages, whereas other plasma proteins are only present in a small proportion of the cells.…”
Section: Morphological Development Of the Choroid Plexus Light Microsmentioning
confidence: 73%
“…The only other systematic cytochemical investigations of the developing choroid plexuses appear to be our studies, carried out mainly in collaboration with Møllgård and colleagues on the distribution of plasma proteins in the human fetus (Jacobsen et al, 1982a,b;Møllgård et al, 1979a) and in fetal sheep (Jacobsen et al, 1983) and our more recent studies of choroid plexus in postnatal Monodelphis domestica (Knott et al, 1997;Li et al 1997). These studies, using immunocytochemistry, showed that a number of common plasma proteins (albumin, fetuin, ␣-fetoprotein, transthyretin, and transferrin) are found in epithelial cells of immature choroid plexuses at all three sites at which choroid plexuses are found, IIIrd, IVth, and lateral ventricles.…”
Section: Morphological Development Of the Choroid Plexus Light Microsmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis of transthyretin by the choroid plexus has only been studied in one American marsupial species: the short‐tailed grey opossum ( Monodelphis domestica) . Synthesis of transthyretin by the choroid plexus was detected during development from the day of birth [81] and in the adult [79].…”
Section: Sites Of Transthyretin Synthesis Throughout Vertebrate Evolumentioning
confidence: 99%
“…However, CP has not been described in the central canal of the spinal cord and thus any possible role not only in the aetiology of recurrent syringomyelia but also in spinal cord development has yet to be addressed. Furthermore, CP may mediate effects of peripheral inflammation in the nervous system by altering gene expression profile after an inflammatory stimulus 14 . On the other hand, systemic non-inflammatory disease may enhance an inflammatory reaction in CP as seen in an autopsy of the CP of two patients treated for diabetic ketoacidosis 15 .…”
Section: A N U S C R I P Tmentioning
confidence: 99%